Analisis Minat Penggunaan Dompet Digital LinkAja dengan Pendekatan Technology Acceptance Model (TAM) di Bandung - Teguh Widodo; Sofia Fauziana Putri (Jurnal Manajemen dan Organisasi, 2021)
The purpose of this study is to analyze the factors that influence the intention to use of digital wallets with an expanded approach of technology acceptance model by adding subjective norms and perceived security as exogenous variables. Subjective norms variable is hypothesized either directly or indirectly through the endogenous variables in TAM to influence intention to use, while perceived security variable is hypothesized to have a direct effect. The hypotheses that have been submitted forms a theoretical framework as structural equation model (SEM). Empirical data was collected through an online survey of 233 respondents who answered 23 questionnaire questions in full. The selection of respondents is determined by purposive—non-probability sampling approach from active users of LinkAja in Bandung whose population is not yet known. The software used to perform the statistical tests of informing that all indicators used meet the criteria of validity and reliability, the ten hypotheses submitted are all accepted based on the t-significance test and strong determining factor. The five TAM variables and their expansion have a positive and significant effect on the intention to use. The biggest influence of antecedent variables on the intention to use sequentially is subjective norms, perceived usefulness, attitude, perceived ease of use, and the smallest is perceived security. In increasing the intention to use, operators should prioritize on increasing subjective norms from prospective users, such as testimonials from role models about the ease of use, convenience, and attractiveness of the digital wallets.